Aspect based opinion mining on restaurant reviews - Tonmoy, Sazid Hasan; Ahmed, Faiyaj Bin; Sarkar, Madhurjya; Bashar, Mehejabin Binta; Ahmed, Rafi (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2023.